Cordyceps yinjiangensis, a new ant-pathogenic fungus - Li, Yu-Ping; Chen, Wan-Hao; Han, Yan-Feng; Liang, Jian-Dong; Liang, Zong-Qi (Phytotaxa, 2020)
Ant-pathogenic fungi are mainly found in the Ophiocordycipitaceae, rarely in the Cordycipitaceae. During a survey of entomopathogenetic fungi from Southwest China, a new species, Cordyceps yinjiangensis, was isolated from the ponerine. It differs from other Cordyceps species by its ant host, shorter phialides, and smaller septate conidia formed in an imbricate chain. Phylogenetic analyses based on the combined datasets of (LSU+RPB2+TEF) and (ITS+TEF) confirmed that C. yinjiangensis is distinct from other species. The new species is formally described and illustrated, and compared to similar species.